2000
DOI: 10.1177/0266666004240288
|View full text |Cite
|
Sign up to set email alerts
|

Digital Library and Information Services in Southern Africa

Abstract: Considers Southern African Development Community (SADC) digital library and information service (LIS) developments and observes an uneven regional pattern, the highlights of which are: though a number of libraries, mostly academic, have Web Online Public Access Catalogues (OPACs), these facilities are generally underdeveloped across the region; South African and Namibian public libraries metadata is accessible on the Internet; regionally, there are a few Internet links to SADC based resources; digital informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…This development has encouraged connectivity to the Internet. For example, all the Southern African Development Community (SADC) countries, made up of Angola, Botswana, Democratic Republic of Congo (DRC), Lesotho, Malawi, Mauritius, Mozambique, Namibia, Seychelles, South Africa, Swaziland, Tanzania, Zambia, and Zimbabwe now have access to the Internet (Muswazi, 2000).…”
Section: Internet Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…This development has encouraged connectivity to the Internet. For example, all the Southern African Development Community (SADC) countries, made up of Angola, Botswana, Democratic Republic of Congo (DRC), Lesotho, Malawi, Mauritius, Mozambique, Namibia, Seychelles, South Africa, Swaziland, Tanzania, Zambia, and Zimbabwe now have access to the Internet (Muswazi, 2000).…”
Section: Internet Connectivitymentioning
confidence: 99%
“…Five academic and three public libraries, and one special library, located in Botswana, Namibia, South Africa, Swaziland and Zambia, have also established Online Public Access Catalogues (OPACs) on the World Wide Web (WWW). However, only the Web pages for academic and public libraries in Botswana, Lesotho, Mozambique, Namibia, South Africa, Zambia, and Zimbabwe are said to indicate links to other Internet information resources (Muswazi, 2000).…”
Section: Internet Connectivitymentioning
confidence: 99%
“…The other problems facing libraries in Sub-Saharan Africa is lack of automation policies. Muswazi (2000) points out that in Botswana, Malawi, Namibia, South Africa and Zimbabwe most university libraries do not have policies on access to OPACS, CDROM, databases, etc. Other problems facing libraries in Africa include high cost of access to electronic databases although it is very difficult to measure the usage of such databases in order to justify such high costs.…”
Section: Challenges Of Deploying Icts In Libraries In Africamentioning
confidence: 99%
“…Chisenga (1998), in a study of use of university libraries home pages, established that there are fairly advanced library information technology in South Africa, Namibia, Botswana, and Zambia. Furthermore, Muswazi (2000), in a study of the digital library and information services in Southern Africa comprising 22 public, 20 academic and five special libraries, found that 10 academic, five special and five public libraries have official home pages. Libraries surveyed in Botswana, Namibia, South Africa, Swaziland and Zambia had OPACS on the World Wide Web, while other libraries in Botswana, Lesotho, Mozambique, Namibia, Zambia and Zimbabwe had extensive links to other resources on the Web (Muswazi, 2000).…”
Section: Library Automation Environment In Africamentioning
confidence: 99%
“…These libraries cannot perform excellently in the face of these daunting problems. This statement was supported by Muswazi (2000), who conducted a survey of fourteen public libraries in Swaziland. He found that information resources were limited in terms of relevance, currency, and volume.…”
Section: Activities Of the Public Librariesmentioning
confidence: 93%